Cone-beam computed tomography analysis of degenerative changes, condylar excursions and positioning and possible correlations with temporomandibular disorder signs and symptoms - Nayara Stefany Leite-; Eduardo Felippe Duailibi-Neto; Israel Chilvarquer; João Gualberto C. Luz (Universidade Estadual de Campinas, 2021)
Aim: To describe cone-beam computed tomography (CBCT) features in patients with temporomandibular disorders (TMDs), in terms of degenerative changes, condylar excursions and positioning as well as their possible correlations with signs and symptoms. Methods: Clinical records of patients diagnosed with TMD who were seen between January 2018 and December 2019 were retrospectively evaluated. These patients were divided into the following groups based on the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD): arthralgia, myalgia, and arthralgia and myalgia groups. The CBCT examination findings of the patients were evaluated in relation to degenerative changes, estimates of condylar excursion, and condylar positioning. The likelihood ratio test was used to verify the possible differences among the three groups, whereas the chi-square test was used to verify the possible differences among the signs and symptoms for the tomographic findings (p ≤ 0.050). Results: In this study, 65 patients with TMD were included. These patients were predominantly female (84.6%) with a mean age of 40.6 years. Tomographic findings of flattening, hyperexcursion and posterior condylar positioning were frequent. A significant correlation was noted between osteophyte and lateral capsule pain (p = 0.027), erosion and posterior capsule pain (p = 0.026), and flattening, pseudocysts (p < 0.050) and condylar excursion (p < 0.001) with mouth opening. Conclusion: Few correlations were noted between degenerative changes and signs of joint pain as well as degenerative changes and condylar hypoexcursion with mouth opening. These correlations were likely associated with division by diagnosis, whereas condylar positioning did not correlate with signs and symptoms.